2023
DOI: 10.20473/jcmphr.v4i2.44661
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Exclusive Breastfeeding History to Stunting Incidence in Children Aged 6-24 Months in The Working Area of The Gunung Anyar Community Health Center, Surabaya, Indonesia

Latiful Elisia,
Risa Etika,
Dwi Aprilawati
et al.

Abstract: Stunting is a linear growth disorder caused by malnutrition from chronic nutrient intake or recurrent chronic infectious diseases, shown by the standard deviation value (SD) unit z (Z-Score) height according to age: < -2 SD ≥ -3 SD. A quantitative cross-sectional design was used for this study. All mothers who visited posyandu in the vicinity of the Gunung Anyar Health Centre, Surabaya, Indonesia with infants aged 6 to 24 months comprised the study sample. Non-probability sampling was done using sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hatijar (2023) indicated that boys tend to experience more stunting due to increased physical activity, leading to higher energy requirements without adequate nutritional intake 11 . The growth process in toddlers is crucial, and a failure to achieve height growth within the first two years may result in stunted growth 12 . The most common age group for mothers in this study was 31 -40 years (57.1%), considered a mature age that can influence child-rearing practices.…”
Section: Discussionmentioning
confidence: 99%
“…Hatijar (2023) indicated that boys tend to experience more stunting due to increased physical activity, leading to higher energy requirements without adequate nutritional intake 11 . The growth process in toddlers is crucial, and a failure to achieve height growth within the first two years may result in stunted growth 12 . The most common age group for mothers in this study was 31 -40 years (57.1%), considered a mature age that can influence child-rearing practices.…”
Section: Discussionmentioning
confidence: 99%